Acute effects of different degrees of ultra‐endurance exercise on systemic inflammatory responses. Issue 1 (January 2015) - Comassi, M.; Vitolo, E.; Pratali, L.; Del Turco, S.; Dellanoce, C.; Rossi, C.; Santini, E.; Solini, A.
Abstract Background Intense physical stress might promote inflammatory responses, whereas a regular physical exercise has positive influence. Little is known on the acute metabolic and inflammatory responses to different levels of strenuous exercise in trained athletes. Aim To compare the short‐term effect of two different ultra‐endurance competitions on the inflammatory profile in male triathletes. Methods We studied 14 Ironman (IR) and 13 Half Ironman (HIR) before and after their own specific race. We assessed body composition and measured blood cells, lipids, iron metabolism and plasma levels of some acute‐phase cytokines and inflammatory markers. Results After the race, IR showed reduced total body water and fat‐free mass, not related with the duration of exercise, and increased white cells and platelets; high‐density lipoprotein levels also increased. IR, but not HIR, showed reduced iron levels, increased ferritin and transferrin, reduced % saturated transferrin. HIR showed higher basal interleukin (IL)‐6, tumour necrosis factor (TNF)‐α, IL‐10, IL‐1β than IR; however, the post‐performance rise was greater in IR. Irisin increased only in HIR and osteocalcin decreased in IR. In the whole study group, delta of white blood cells was directly related with delta of monocyte chemoattractant protein 1, and Δ ferritin was inversely related with Δosteocalcin. Conclusions A single ultra‐endurance competition induces an inflammatory response depending on the duration of physical effort, with increased acute‐phase cytokines, and an altered iron metabolism. Irisin, whose biological meaning is still uncertain, seems to be associated with acute variations of some metabolic parameters.